The Implications of the Implementation of the ASEAN Framework Agreement on Services (AFAS) on Notarial Territorial Jurisdiction: A Comparative Study of Indonesia and Malaysia - Sanjaya, Alya Afiffa Raihana Nissa (Universitas Islam Negeri Sumatera Utara, 2026)
Economic integration within ASEAN through the ASEAN Framework Agreement on Services (AFAS) has promoted the liberalization of professional services across member states; however, legal scholarship remains limited in examining its implications for professions that embody public authority, particularly notaries operating under different legal systems. This study aims to analyze the implications of AFAS on notarial territorial jurisdiction through a comparative analysis of Indonesia and Malaysia. Employing a normative juridical method with statutory, conceptual, and comparative approaches, this research examines the regulatory frameworks governing notarial authority in both countries. The findings reveal that AFAS produces asymmetric implications for the notarial profession. In Indonesia, notaries function as public officials whose authority is strictly territorial and grounded in state sovereignty, thereby restricting the application of service liberalization. In contrast, Malaysian notary public operate as private legal professionals with administrative functions, enabling greater flexibility in cross-border service provision. The novelty of this study lies in its argument that service liberalization under AFAS cannot be uniformly applied to professions with public functions, necessitating a differentiated legal harmonization model to ensure legal certainty while preserving national sovereignty within the ASEAN integration framework.